Parameters affecting acetate concentrations during in-situ biological hydrogen methanation. (June 2018) - Agneessens, Laura Mia; Ottosen, Lars Ditlev Mørck; Andersen, Martin; Berg Olesen, Christina; Feilberg, Anders; Kofoed, Michael Vedel Wegener
Graphical abstract: Highlights: Acetate accumulation increases at increasing organic loading rates. Homoacetogenesis consumes up to 60% of applied H2 at low CO2 levels. Homoacetogenesis becomes less important after repeated H2 injections. These parameters may be used to assess acetate kinetics during H2 injections. Abstract: Surplus electricity may be supplied to anaerobic digesters as H2 gas to upgrade the CH4 content of biogas. Acetate accumulation has been observed following H2 injections, but the parameters determining the degree of acetate accumulation are not well understood. The pathways involved during H2 consumption and acetate kinetics were evaluated in continuous lab reactors and parallel batch 13 C experiments. Acetate accumulation increased during initial H2 injections as organic loading rate increased and CO2 levels decreased below 7%. The share of CH4 in H2 and 13 C mass balances increased after repeated H2 injections, which corresponded with the increase of Methanomicrobiales observed via qPCR. The organic loading rate, the inorganic carbon level and level of methanogen adaption hence determine acetate kinetics during biomethanation of H2 . The three identified parameters may form the base of a decision tool to assess acetate accumulation during H2 injections to an anaerobic digester.